2000
DOI: 10.1021/bc0000740
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Derivatives of Peptide Nucleic Acid (PNA) OligomersSynthesis, Characterization, and DNA Binding

Abstract: This work describes the first automated solid-phase synthesis of metal derivatives of peptide nucleic acid (PNA) oligomers and their interaction with DNA and PNA. PNA constitutes a relatively young and very promising class of DNA analogues with excellent DNA and RNA binding properties. However, PNA lacks a suitable handle that would permit its sensitive detection on its own as well as when hybridized with complementary oligonucleotides. Metal complexes, on the other hand, offer high potential as markers for bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 19 publications
1
78
1
1
Order By: Relevance
“…UV/Vis and emission spectra measurements on these monomers M1 and M2 and their respective intermediates, 1 2, 4 and 5 show similar behaviour to those that have been reported previously by our group and by Metzler-Nolte and co-workers. [23,32,44] Electrochemical measurements showed that all complexes give rise to a reversible one-electron Ru II /Ru III process. The in-sertion of a linker group between the metal center and the PNA unit in M2 relative to M1 only has a small effect on the luminescence and electrochemistry of the ruthenium complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…UV/Vis and emission spectra measurements on these monomers M1 and M2 and their respective intermediates, 1 2, 4 and 5 show similar behaviour to those that have been reported previously by our group and by Metzler-Nolte and co-workers. [23,32,44] Electrochemical measurements showed that all complexes give rise to a reversible one-electron Ru II /Ru III process. The in-sertion of a linker group between the metal center and the PNA unit in M2 relative to M1 only has a small effect on the luminescence and electrochemistry of the ruthenium complex.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Subsequently, the same group described the attachment of a tris(bipyridine) Ru II complex to a PNA heptamer where the metal centre had been inserted to the amino end of the sequence by automated synthesis. [32] On hybridisation of this Ru II -bearing PNA heptamer with a complementary DNA strand, the CD (circular dichroism) spectra showed a positive Cotton effect by a shift in the maximum from 266 nm (PNA.DNA bioconjugate) to 280 nm (Ru-PNA-DNA bioconjugate). [32] Metal-containing PNAs have also been synthesised by Achim et al for purposes that include investigation of the electron transfer within PNA [33] and the increase in PNA-DNA stability through metal binding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[24] Die Resultate zeigen wie erwartet eine Duplexbildung von 5·7 (Schmelztemperatur T m = 29.7 8C) und 6·7 (T m = 36.1 8C, siehe auch Hintergrundinformationen, Abbildung S1). Die Differenz DT m = 6.3 8C schreiben wir einer anziehenden elektrostatischen Wechselwirkung zwischen dem positiv geladenen NLS-Peptid und dem überhängenden, negativ geladenen 5'-Ende der DNA im Duplex 6·7 zu.…”
unclassified